Long-Term Viral Brain-Derived Neurotrophic Factor Delivery Promotes Spasticity in Rats with a Cervical Spinal Cord Hemisection - Fouad, Karim; Bennett, David; Vavrek, Romana; Blesch, Armin (Frontiers in Neurology, 2013)
We have recently reported that rats with spinal cord injury (SCI) that received a combinatorial treatment, including viral BDNF delivery in the spinal cord, did not only show enhanced axonal regeneration, but also deterioration of hindlimb motor function. By demonstrating that BDNF over-expression can trigger spasticity-like symptoms in another rat model of spinal cord injury (SCI), we proposed a causal relationship between the observed spasticity-like symptoms (i.e., resistance to passive range of motion) and the over-expression of BDNF. The current study was originally designed to evaluate a comparable combined treatment to rats with cervical SCI to improve motor recovery. Once again we found similar signs of spasticity, involving clenching of the paws and wrist flexion. Using electromyographic measurements changed the focus of the study and explored whether this spasticity like symptom is directly related to the over-expression of BDNF by administering a BDNF antagonist. In an acute experiment this treatment gradually diminished the resistance to overcome forelimb flexion. Thus, we conclude that neuro-excitatory effects of chronic BDNF delivery together with diminished descending control after SCI can result in adverse effects.